Gene Delivery to Mammalian Cells - Heiser, William C;Ed (Humana Press, 2004)
Whether to assess the function of new genes identified from the Human Genome Project or to apply gene therapy successfully, it is often necessary to deliver genes to specific cells. In Gene Delivery to Mammalian Cells, highly experienced researchers describe in great detail methods that have proven most useful in delivering genes to mammalian cells. Volume 2: Viral Gene Transfer Techniques details procedures for delivering genes to cells in vitro and in vivo, including the use of lentiviral vectors, adenovirus, adeno-associated viruses, alphavirus, herpes simplex virus, baculovirus, and retrovirus. Many of these techniques have only been in practice for a few years and are still being refined and updated. Some are being used not only in basic science, but also in gene therapy applications. Each protocol contains step-by-step instructions, along with background notes, equipment and reagent lists, and tips on troubleshooting and avoiding known pitfalls. Introductory chapters review the delivery methods presented, discussing their advantages and disadvantages, how they have been used successfully for gene delivery, and the future of their technology. An accompanying volume, Volume 1: Nonviral Gene Transfer Techniques, focuses on gene delivery by a variety of chemical and physical methods. Comprehensive and cutting-edge, Gene Delivery to Mammalian Cells, volumes 1 and 2, offers biomedical specialists in industry and academia an unrivaled collection of reliable methods for the chemical, physical, and viral delivery of genes to mammalian cells, all prepared to save laboratory time and ensure experimental success.